Integrated Pest Management (IPM) of the Caribbean Crazy Ant, Nylanderia (=Paratrechina) pubens (Forel) - Dawn Calibeo; Faith Oi (EDIS)
Incidents of Caribbean crazy ant infestations are on the rise! These highly active ants are annoying to residents and pets. And, they can cause short circuits and power outages if they infest electrical equipment. Learn how to identify and apply the principles of integrated pest management (IPM) to deal with these difficult pests in this 4-page fact sheet written by Dawn Calibeo and Faith Oi and published by the UF Department of Entomology and Nematology, July 2011.